Effect of COVID-19 Pandemic Anxiety and Nutrition Against the Expenditure of Mother's Milk in Postpartum Mothers at the Regional General Hospital Mgr. Gabriel Manek, SVD Atambua - Maria Argensah Dos Santos; Yenny Puspitasari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze effect of coronavirus disease 2019 (COVID-19) pandemic anxiety and nutrition against the expenditure of mother's milk in postpartum mothers at the Regional General Hospital Mgr. Gabriel Manek, SVD Atambua. In this study using analytical survey research with a quantitative approach. The design used is observational using a cross sectional approach. The population used in this study are all postpartum mothers on the first day in the orchid room. Samples from the first postpartum day in the orchid room are 105 postpartum mothers. Testing research problems using calculations assisted using the Statistical Program for Social Science (SPSS). The results show that COVID-19 pandemic anxiety and nutrition have an effect against the expenditure of mother's milk in postpartum mothers at the Regional General Hospital Mgr. Gabriel Manek, SVD Atambua.